Coupled metabolic‐hydrodynamic modeling enabling rational scale‐up of industrial bioprocesses. Issue 3 (20th December 2019) - Wang, Guan; Haringa, Cees; Tang, Wenjun; Noorman, Henk; Chu, Ju; Zhuang, Yingping; Zhang, Siliang
Abstract: Metabolomics aims to address what and how regulatory mechanisms are coordinated to achieve flux optimality, different metabolic objectives as well as appropriate adaptations to dynamic nutrient availability. Recent decades have witnessed that the integration of metabolomics and fluxomics within the goal of synthetic biology has arrived at generating the desired bioproducts with improved bioconversion efficiency. Absolute metabolite quantification by isotope dilution mass spectrometry represents a functional readout of cellular biochemistry and contributes to the establishment of metabolic (structured) models required in systems metabolic engineering. In industrial practices, population heterogeneity arising from fluctuating nutrient availability frequently leads to performance losses, that is reduced commercial metrics (titer, rate, and yield). Hence, the development of more stable producers and more predictable bioprocesses can benefit from a quantitative understanding of spatial and temporal cell‐to‐cell heterogeneity within industrial bioprocesses. Quantitative metabolomics analysis and metabolic modeling applied in computational fluid dynamics (CFD)‐assisted scale‐down simulators that mimic industrial heterogeneity such as fluctuations in nutrients, dissolved gases, and other stresses can procure informative clues for coping with issues during bioprocessing scale‐up. In previous studies, only limited insights into the hydrodynamic conditions inside the industrial‐scale bioreactor have been obtained, which makes case‐by‐case scale‐up far from straightforward. Tracking the flow paths of cells circulating in large‐scale bioreactors is a highly valuable tool for evaluating cellular performance in production tanks. The "lifelines" or "trajectories" of cells in industrial‐scale bioreactors can be captured using Euler‐Lagrange CFD simulation. This novel methodology can be further coupled with metabolic (structured) models to provide not only a statistical analysis of cell lifelines triggered by the environmental fluctuations but also a global assessment of the metabolic response to heterogeneity inside an industrial bioreactor. For the future, the industrial design should be dependent on the computational framework, and this integration work will allow bioprocess scale‐up to the industrial scale with an end in mind. Abstract : We have proposed a computational framework (computational fluid dynamics‐computational reaction dynamics [CFD‐CRD] analysis) to accelerate industrial‐scale bioprocess design. The "lifelines" or "trajectories" of cells in industrial‐scale bioreactors can be captured using Euler‐Lagrange CFD simulation. This novel methodology can be further coupled with metabolic (structured) models to provide not only a statistical analysis of cell lifelines triggered by the environmental fluctuations but also a global assessment of the metabolic response to heterogeneity inside an industrial bioreactor.